Quantification of two isomeric flavones in rat colon tissue using reverse phase high performance liquid chromatography (2017)
Background Antineoplastic activity has been previously shown for two isomeric flavones, 5,7-dihydroxy-3,6,8-trimethoxy flavone (flavone A) and 3,5-dihydroxy-6,7,8-trimethoxy flavone (flavone B), against colon cancer cell lines (Thomas et al. in PLoS ONE 7:e39806, 5). Here, we present modified methods for the extraction and quantification of flavones A and B in rat colon tissue after intravenous dosing via high performance liquid chromatography, from the originally described procedure for extraction and quantification in rat plasma (Whitted et al. in J Chromatogr B Analyt Technol Biomed Life Sci 1001:150–155, 7). Results Modifications included tissue homogenization (1 g tissue: 2 mL water), filtration of the supernatant with a PVDF membrane, and the use of only one calibration curve to determine the concentration of each flavone in colon tissue. Good separation was achieved and representative equations were linear with r 2 ≥ 0.99 for both flavones. Precision and accuracy for flavone A ranged from 0.88–24.03 and 109–116%. Precision and accuracy for flavone B ranged from 1.62–33.56 and 98–113%. Concentrations of 1639 ± 601 ng/g flavone A and 5975 ± 2480 ng/g of flavone B were detected in rat colon tissue 6 h post dosing. Conclusions Modifications to the extraction methods for flavone A and flavone B from rat colon tissue had good separation, precision, and accuracy.